Beyond the golden lotus : Chin P'ing Mei - Ding, Yaokang, 1599-1669.; Kean, Vladimir; Xiaoxiaosheng (London ; New York : Kegan Paul ; Biggleswade, UK : Distributed by Extenza-Turpin ; New York : Distributed by Columbia University Press, 2004)
First published in 2005. Routledge is an imprint of Taylor & Francis, an informa company.
13. The scurvy Lover breaks Faith for the sake of filthy Lucre. The foolish Maiden keeps her Oath to her unworthy Lover, even unto Death14. The careless Coxcomb falls into a Trap in the Course of an Excursion in the Country; 15. The Maid Cherry, ever faithful to her erstwhile Mistress, throws herself into the River. Losing all Sense of Shame and Honour, the degenerate Offspring of a noble Family sinks to the Level of a Street Musician and begs for his daily Bread.
"Sequel to: Chin P'ing Mei"--Cover.
Translated from the Chinese.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: China -- History -- Song dynasty, 960-1279 -- Fiction; China -- Social conditions -- 960-1644 -- Fiction; FICTION -- General; Social conditions; Song Dynasty (China); China; 960-1644; Domestic fiction; Electronic books; Domestic fiction; Fiction; History